Three new species of Tmesiphorini (Coleoptera: Staphylinidae: Pselaphinae) from the Nanling Mountains, China - Zhang, Yong-Qin; Yin, Zi-Wei (Zootaxa, 2024)
Three new tmesiphorine species from the Nanling Mountains, Raphitreus septuacarinatus sp. nov., Tmesiphorus huapingensis sp. nov., and Tmesiphorus maoermontis sp. nov., are described, with illustrations of the habitus and diagnostic features. All species can be readily separated from congeners by the unique male characters as well as structure of the aedeagus. A key to genera of Tmesiphorini from Nanling is provided.